2008
DOI: 10.1186/cc6883
|View full text |Cite
|
Sign up to set email alerts
|

Eosinopenia is a reliable marker of sepsis on admission to medical intensive care units

Abstract: Introduction Eosinopenia is a cheap and forgotten marker of acute infection that has not been evaluated previously in intensive care units (ICUs). The aim of the present study was to test the value of eosinopenia in the diagnosis of sepsis in patients admitted to ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
198
5
26

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(234 citation statements)
references
References 39 publications
5
198
5
26
Order By: Relevance
“…One study found that sepsis survivors had a trend toward elevated levels of IL-5 compared with nonsurvivors (23). However, sepsis and bacterial infections are associated with a marked eosinopenia (24,25). This apparent paradox suggests differential and independent functions for eosinophils and IL-5 in sepsis.…”
mentioning
confidence: 99%
“…One study found that sepsis survivors had a trend toward elevated levels of IL-5 compared with nonsurvivors (23). However, sepsis and bacterial infections are associated with a marked eosinopenia (24,25). This apparent paradox suggests differential and independent functions for eosinophils and IL-5 in sepsis.…”
mentioning
confidence: 99%
“…In a prospective study, eosinopenia (<40 cells/mm 3 ) was a good diagnostic tool for distinguishing between non-infection and infection in the intensive care unit (ICU), while it was a moderate marker for discriminating between systemic inflammatory response syndrome and infection in newly admitted critically ill patients. (8) In that study, the AUROC was 0.89 for eosinophils and 0.77 for CRP for discriminating between non-infection and infection. Shaaban et al (14) found that the AUROC for eosinopenia (<50 cells/mm 3 ), high CRP (>70 mg/L), and high procalcitonin (>1.5 μg/L) for discriminating between non-infection and infection in the adult critical care unit were 0.72, 0.92, and 0.89, respectively.…”
Section: The Upper Limit Of Eosinophils In Blood Is 350 Cells/mm 3 (1mentioning
confidence: 78%
“…(5-7) Furthermore, procalcitonin testing is very expensive and is seldom available in emergency departments in developing countries such as Turkey. (8) In 1893, Zappert (9) first described marked reduction in the number of circulating eosinophils in acute infection, and it was utilized as a useful diagnostic sign during the first quarter of the last century. (10) After observing that eosinopenia is part of the normal response to stress, (11) it was assumed that the eosinopenia of acute infection is a secondary response to stress caused by the infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A STAT3 gene analysis was required to precisely differentiate HIES in this case because some cases of HIES in patients without characteristic facies or bone and connective tissue abnormalities have been reported. In addition, eosinopenia has recently been reported to be a marker of sepsis (9), leading us to suspect that the current patient's low eosinophil count on admission may have been caused by a sepsis-like condition.…”
Section: Discussionmentioning
confidence: 95%